Rural land rights reform and agro-environmental sustainability: Empirical evidence from China. (May 2018) - Xu, Yuting; Huang, Xianjin; Bao, Helen X.H.; Ju, Xiang; Zhong, Taiyang; Chen, Zhigang; Zhou, Yan
Abstract: The landscape of China's rural land market has been changed by several significant land right reforms since the 1970s. It is always of great interest to both the government and the public to gauge the effectiveness of these reforms. We address this question by investigating the impact of a recent land use right reform, namely, the 'Three Rights Separation Policy', on agro-environmental sustainability. By separating land management right from land contracted management right, this new reform is believed to be a powerful tool to encourage land transfer, optimize land resource allocation, and increase the economy of scale in the agriculture sector. Using a PSM-DID model applied to panel data for the years 2008 and 2014, our study demonstrates that the new policy also increases the use of organic fertilizers by 48.641 kg/mu in total, which is a very important step to ensure agro-environmental sustainability in China. The new policy is more effective in encouraging the application of organic fertilizer when the issuing of land certificates is enforced and administrative barriers to land right transfers are removed. The findings add value to the growing literature on rural land right reforms in China and may also have significant implications in developing countries with similar rural land tenure systems and underdeveloped land and labor markets.